Sharia-Based Transformational Leadership and Employee Loyalty: The Mediating Role of Psychological Empowerment in Indonesian Public Sector Organizations - Tamriatin Hidayah; Hamzah Fansuri Yusuf; Pawestri Winahyu (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
Employee loyalty has become an increasingly important challenge in Indonesian public sector organizations, particularly among non-civil servant employees who experience employment insecurity, limited career advancement opportunities, and disparities in organizational benefits. Although transformational leadership has been widely recognized as a determinant of employee loyalty, limited empirical evidence explains how Sharia-Based Transformational Leadership, grounded in Islamic ethical values, influences employee loyalty through psychological empowerment. This study aims to examine the direct effects of Sharia-Based Transformational Leadership, compensation, and perceived organizational support on employee loyalty and psychological empowerment, as well as the mediating role of psychological empowerment. A quantitative explanatory design was employed using survey data collected from 477 non-civil servant employees in local government organizations in Jember Regency, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Sharia-Based Transformational Leadership, compensation, and perceived organizational support significantly enhance psychological empowerment and employee loyalty. Psychological empowerment also serves as a significant mediator between the antecedent variables and employee loyalty. These findings extend Social Exchange Theory by integrating Islamic ethical leadership principles and suggest that strengthening Sharia-based leadership practices, equitable compensation, and organizational support can foster sustainable employee loyalty in Indonesian public sector organizations.